RANCANG BANGUN APLIKASI E-RECRUITMENT KARYAWAN BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING PADA PT. HSEO TEKNO MEDIA - Andika Eka Wardana; Nardiono (CV. Multi Kreasi Media, 2025)
Along with the development of technology today which is increasingly rapid so that all human needs are inseparable from the role of technology, especially in the field of information. There are already many companies that utilize technology in the field of information, one of which is an activity in recruiting employees. Employees are a very important asset for a company to achieve its goals. To get qualified employees, a proper recruitment process is needed. In this case, the aspect of recruiting employees is very important for every company. The current employee recruitment system at PT. Hseo Tekno Media still uses a conventional system. As a solution to overcome this problem, the author conducted a study that aims to transform conventional systems into modern systems by creating a web-based e-recruitment application.In its development, the author uses an extreme programming approach method so that the application produced is in accordance with the needs of the user. The application uses Python and PostgreSQL programming languages as databases to store data. The results of this study are in the form of a web-based e-recruitment application so that it can help HRD in managing employee data.